CCAFS Gender and Social Inclusion Strategy - Huyer, Sophia; Campbell, Bruce M.; Hill, Catherine; Vermeulen, Sonja J. (2016)
The CCAFS Gender and Social Inclusion (GSI) Strategy is an update of the CCAFS 2012 Gender Strategy. The new strategy addresses gender as well as social inclusion for different social groups while bearing in mind that women are central to agriculture in developing countries. The CCAFS approach to GSI allies with the CGIAR objectives to create opportunities for women, young people and marginalized groups and to promote equitable access to resources, information and power in the agri-food system for men and women in order to close the gender gap by 2030.